The Forbidden Reel: Documentary by Ariel Nasr - Seller, Shyla (Archivaria, 2020)
The Forbidden Reel. Documentary, directed by Ariel Nasr. Loaded Pictures and National Film Board of Canada, 2019. 120 min. (2K DCP). DOXA 2020 Documentary Film Festival, Vancouver and online, June 18–26, 2020; Hot Docs Festival Online, Toronto and online, May 28 – June 24, 2020.